Ethical marketing and the new consumer - Arnold, Chris. (Wiley, 2009)
Ethical marketing isn't just about environmentalism, it's far bigger than that. This book challenges a lot of conventional thinking and introduces you to a wider range of ethics and the many types of ethical consumers. --from publisher description.